The Importance of Antibiotic Sensitivity to the Gene in Medical Practice and the Relevance of Combating Them - Abdullaevna, Kuralay Kadirova; qizi, Mubinabonu Norqulova Turg‘un; qizi, Nigina Murodova Ilyos (American Journal of Bioscience and Clinical Integrity, 2025)
Since their discovery in the early 1900s, antibiotics have transformed medicine and saved countless lives. However, the worrying increase in antibiotic resistance has eclipsed the history of antibiotics. The unrelenting adaptability of microbes, which is fueled by antibiotic abuse and overuse, is the cause of this global issue. The history of antibiotics and the following rise of antibiotic resistance are examined in this article. It explores the methods bacteria use to become resistant, emphasizing the grave repercussions of medication resistance, such as worse patient care, higher death rates, and rising medical expenses. The article describes the most recent tactics for combating drug-resistant microbes, including cutting-edge methods like phage treatment, CRISPR-Cas9 technology, and the investigation of natural substances. Additionally, it looks at how antibiotic resistance significantly affects medication development, making the search for new antibiotics financially difficult. The restrictions and difficulties in creating new antibiotics are examined, as well as regulatory roadblocks that impede advancement in this vital area. There are suggestions for altering the regulatory procedure to speed up the creation of antibiotics. Major pharmaceutical companies’ departure from antibiotic research is discussed, as well as possible ways to pique their interest again. The article highlights global alliances and collaborations while outlining efforts to address economic obstacles and encourage the development of antibiotics. Lastly, the essay discusses government-led efforts to combat antibiotic resistance, with a particular emphasis on the Middle East. It talks on the proactive steps regional governments, like those in the more countries, have made to counter this worldwide menace. A diversified strategy is essential in the face of antibiotic resistance. This article offers insightful information about the intricate world of antibiotic development, the difficulties with regulations, and the teamwork needed to guarantee that antibiotics continue to be useful instruments for preserving public health in the future.